Do we need a new approach to R&D works in financial reporting? - Artur Hołda; Paweł Łojek (Central European Economic Journal (CEEJ), 2024)
Research and Development works (RD works) in accounting is increasingly used both in Poland and globally. The potential benefit of numerous tax breaks is an incentive to implement innovative solutions. The article aims to verify research hypotheses through a chi2 independence test concerning the need to create a new national accounting standard regarding RD works and the respondents' knowledge of balance sheet and tax law. Questions were also raised regarding RD works expenses. The findings suggest that the respondents do not feel the need to create a new national accounting standard. However, respondents' knowledge of the relevant issues is relatively limited, both in terms of balance sheet law and tax law. Moreover, it was established that a tax audit should be anticipated when utilizing tax reliefs, not always from the co-financing institution. This study contributes to the ongoing perception of RD works by accountants and managers and may also serve as a foundation for further research with a larger research sample.
Keywords: M16; M41; 330; balance sheet and tax law; R&D Classification